ANALYSIS OF THE IMPLEMENTATION OF PPK-BLUD IN ORDER TO ASSESS THE FINANCIAL PERFORMANCE OF THE CASE STUDY AT DRS. H. AMRI TAMBUNAN IN DELI SERDANG REGENCY - Ika Monalisa Tambunan; Heriyati Chrisna; Nina Andriany Nasution (Yayasan Multidimensi Kreatif, 2025)
This study uses a quantitative method with a descriptive approach that aims to find out and evaluate the financial performance of Drs. H. Amri Tambunan Hospital, Deli Serdang Regency in 2019-2023. The object of this study is financial statements in the form of balance sheets, operational reports, cash flows, budget realization reports and notes on financial statements. The financial performance in this study was calculated using financial ratio parameters consisting of cash ratio, current ratio, collection period, fixed asset turnover, return on fixed assets, return on equity, inventory turnover, PNBP income ratio to operational costs, and the ratio of patient cost subsidies. The results of the study show that in 2019 the resulting financial performance achievement was 56.58% and obtained the